Tobacco quitline staffs' knowledge and attitudes about connecting quitline callers to lung cancer screening educational materials - Naomi Q. P. Tan; Robert J. Volk; Viola B. Leal; Jessica S. Lettieri; Linda A. Bailey; Thomas Ylioja; Paula Celestino; Lisa M. Lowenstein (Cancer Medicine, 2024)
Abstract Objective To evaluate the impact of training quitline staff in lung cancer screening (LCS) on knowledge and attitudes towards connecting quitline callers to LCS educational materials. Methods We conducted a pre‐post evaluation within a larger implementation project in the U.S. to support LCS among quitline callers. From July 2020 to June 2021, staff from four quitline service providers completed surveys before and after training on LCS knowledge. After training, staff completed the acceptability of intervention measure, intervention appropriateness measure, and feasibility of the intervention measure. Results A total of 245 staff completed the initial demographic survey (analytic sample), 130 completed the pre‐training survey, and 225 completed the post‐training survey. Staff were on average 47.4 years old and 76.7% were female. LCS knowledge improved after the training (n = 120, mean difference = +26.5%, 95% CI 21.6, 31.4, p < 0.001). Overall, staff felt that connecting quitline callers to LCS education materials was acceptable (M = 4.0, SD = 0.8), appropriate (M = 4.1, SD = 0.7), and feasible (M = 4.0, SD = 0.7). Conclusions Receiving training about LCS eligibility and the benefits and harms of screening improved LCS knowledge among quitline staff. Quitline staff found that connecting callers with LCS educational materials is acceptable, appropriate, and feasible, and aligned with their primary mission.